PENINGKAT EFEKTIVITAS BERKOMUNIKASI DAN HASIL BELAJAR SISWA KELAS IV PADA PEMBELAJARAN IPA MELALUI MODEL OPEN ENDED DI SDN 26 KAMPUNG AUR KAB PESISIR SELATAN - santika, mira; gusmaweti, gusmaweti; amrina, zulfa (Perspektif, 2019)
The purpose of this study was to describe the increase in the effectiveness of communication and learning outcomes of fourth grade students in learning science through the Open Ended in SDN 26 Kampung Aur, this type of research is a class act, with the subject of the fourth grade students of SDN 26 Kampung Aur, which has 21 students. Research was conducted in the second semester of the school year of 2015/2016, the research instrument used is the effectiveness of communicating student sheets, sheets of assessment of learning outcomes in the cognitive aspects of students at level C1 (knowledge) and C2 (understanding). Based on the research results, the effectiveness of communicating students on the aspects asked in the first cycle obtain an average value of 49.99% increase in cycle II to 67.45%, the effectiveness of communicating students on aspects of the answer in the first cycle obtain an average value of 53.96% increased in the second cycle to 71.42%. While the results of student learning at the cognitive level C1 (knowledge) in the first cycle increase in cycle II 68.33 into 80.47, cognitive learning outcomes in level C2 (understanding) in the first cycle increase in cycle II 58.09 to 71.42 , It can be concluded that the Open Ended learning model can increase the effectiveness of communication and student learning outcomes in science teaching fourth grade SDN26 Kampung Aur.Keywords: Communicating Effectiveness, Results Learning, Model Open Ended, IPA